Crowding Out and Crowding in within Keynesian Framework. Do We Need Any New Empirical Research Concerning Them? - Adam P. Balcerzak; Elzbieta Rogalska (Institute of Economic Research (IER), 2014)
Last global financial crisis resulted in common among developed countries implementation of expansionary fiscal policy as an anti-recession tool. This led to the renewal of academic discussion on stabilization effectiveness of fiscal policy. In this context, the main research goal of this paper is to give theoretical analysis of the determinants of counter-cyclical effectiveness of fiscal policy with special concentration on crowding out and crowding in effects. Methodologically the analysis is done within Keynesian IS-LM framework within the assumption of expectations of economic actors. The theoretical analysis is confronted with the review of empirical papers based on the experiences of developed countries.
Keywords: E62; H31; H32; 330; fiscal policy; crowding out; crowding in; stabilization policy